Taking God at his word : why the Bible is knowable, necessary, and enough, and what that means for you and me - DeYoung, Kevin (Wheaton, Illinois : Crossway, 2014)
Kevin DeYoung has written an accessible introduction to the Bible that answers important questions raised by Christians and non-Christians. This book will help you understand what the Bible says about itself and the key characteristics that contribute to its lasting significance. --from publisher description
Includes bibliographical references and indexes
Keywords: Bible -- Evidences, authority, etc; Bible -- Inspiration